The development of history educational game as a revision tool for Malaysia school education - Abd Razak, Abd Hadi; Wan Daud, Wan Mohd Fazdli; Ibrahim, Nurulhuda (2011)
Computer game has indisputably become a culture especially among teenagers even in Malaysian community.Through the use of broadband and civilizing of IT usage, teenagers have now been exposed to computer game since at young age.A decade ago, computer game was perceived as only a medium for students to seek pleasure without giving any benefit to them.Recently, various attempts have been arranged to enable computer game to be incorporated into classroom to make learning experience more interesting and enjoyable.As a result, an educational computer game prototype has been developed for the purpose of meeting these requirements. The prototype, which is dedicated for the history subject for Malaysia secondary school, mainly serves as a revision tool for the student.MUDPY model has been employed as the main methodology for the project.The prototype was tested using the black box test to ensure the functionality and PUEU test for the effectiveness.This paper exposes the techniques used for development and the findings resulted from the tests conducted.